2008
DOI: 10.1037/0022-3514.95.2.319
|View full text |Cite
|
Sign up to set email alerts
|

How goal instrumentality shapes relationship evaluations.

Abstract: Findings from 6 experiments support the hypothesis that relationship evaluations and behavioral tendencies are goal dependent, reflecting the instrumentality of significant others for the self's progress toward currently active goals. Experiments 1 and 3 found that active goals can automatically bring to mind significant others who are instrumental for the activated goal, heightening their accessibility relative to noninstrumental others. Experiments 2-5 found that active goals cause individuals to evaluate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
297
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(310 citation statements)
references
References 53 publications
12
297
1
Order By: Relevance
“…Again, there was an appraisable outcome (whether participants detected the target combination or not) and an evaluator (the experimenter). In a similar vein, Fitzsimons and Shah (2008) demonstrated that names of other people who are instrumental for achieving a specific goal are more easily accessible when the goal is activated. Again, information that may help to realize an intention successfully was more easily accessible.…”
Section: Discussionmentioning
confidence: 91%
“…Again, there was an appraisable outcome (whether participants detected the target combination or not) and an evaluator (the experimenter). In a similar vein, Fitzsimons and Shah (2008) demonstrated that names of other people who are instrumental for achieving a specific goal are more easily accessible when the goal is activated. Again, information that may help to realize an intention successfully was more easily accessible.…”
Section: Discussionmentioning
confidence: 91%
“…Search volume indices were then summed within each group, and the three resulting curves were standardized so that their peaks would be equal. 8 MASICAMPO AND AMBADY respond to individuals' shifting needs in similar ways (e.g., DeWall et al, 2011;Fitzsimons & Shah, 2008;Maner et al, 2009). Thus, we do not consider the shared forms that we observed in the present work to be mere coincidence but rather to be a product of shared, underlying mechanisms between individual-level memory and widespread interest.…”
Section: Discussionmentioning
confidence: 99%
“…Once the goal has been attained and the actor has moved on to other pursuits, appreciation for the instrumental partner tends to wane (Converse & Fishbach, 2012;Fitzsimons & Shah, 2008;Fitzsimons & Fishbach, 2010;Fitzsimons, Friesen, Orehek, & Kruglanski, 2009). One challenge for maintaining interpersonal closeness, then, is to transform these momentary experiences of appreciation into lasting sentiments.…”
Section: Relationship Initiation and Evaluationmentioning
confidence: 99%